A Pragmatic Study on Locative Deixis in the Dompu Language - HD, Moh. Imam; Hartinah, Yulmi (SUAR BETANG, 2024)
This research aims to describe the form and function of locative deixis in the Dompu language. The data is in the form of transcriptions of Dompu language verbal speech containing locative deixis. The data for this research come from the people who live in Dompu Regency and speak the Dompu language. This is a descriptive qualitative research. The data collection technique used is listening and listening technique. The research results show that the form of locative deixis in the Dompu language can be divided into two. First, deixis in the form of the directions da ‘north', ele ‘east’, do ‘south’, and di ‘west’ followed by the name of the referent. Directional deixis functions to designate places that are near or far from the speaker. Second, deixis is in the form of indicating the positions ese ‘above’, awa ‘below’, dei ‘inside’, and ari ‘outside’ followed by the name of the referent. Positional deixis functions to designate places far from the speaker.